2007
DOI: 10.1007/s11695-007-9323-8
|View full text |Cite
|
Sign up to set email alerts
|

Peptide YY and Glucagon-like Peptide-1 in Morbidly Obese Patients Before and After Surgically Induced Weight Loss

Abstract: In morbidly obese adults reducing their weight by bariatric surgery, fasting PYY levels increased and GLP-1 concentrations decreased independently of each other. Therefore, the relationship between PYY and GLP-1 seems more complicated than might be anticipated from animal and in vitro studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 33 publications
3
51
0
2
Order By: Relevance
“…96 Low bone mass was observed in PYY gene knockout models. 100 PYY levels increase after RNYGB and biliopancreatic diversion, 101 adjustable gastric band, 102 and sleeve gastrectomy. 103 To our knowledge, no clinical study to date has correlated PYY levels with bone density in bariatric surgery patients.…”
Section: Impact Of Bariatric Surgery On Bone Metabolismmentioning
confidence: 97%
“…96 Low bone mass was observed in PYY gene knockout models. 100 PYY levels increase after RNYGB and biliopancreatic diversion, 101 adjustable gastric band, 102 and sleeve gastrectomy. 103 To our knowledge, no clinical study to date has correlated PYY levels with bone density in bariatric surgery patients.…”
Section: Impact Of Bariatric Surgery On Bone Metabolismmentioning
confidence: 97%
“…CCK analysis used Phoenix Peptidese RIA (RK-069-04) for CCK octapeptide (CCK [26][27][28][29][30][31][32][33]. The standard RIA protocol was applied but without extraction of the peptides before the assay.…”
Section: Clinical Indicesmentioning
confidence: 99%
“…Indeed, most data support this theory, showing increased levels of GLP-1, PYY, and oxyntomodulin (OXM) after RYGB operation [26,27]. However, in one study, a decrease in GLP-1 levels was observed after bariatric surgery of morbidly obese adults [28]. …”
Section: The Role Of Eecs In Bariatric Surgerymentioning
confidence: 99%